Asia through art and anthropology
1 online resource (256 pages)
Keywords: * AWARDED BEST ANTHOLOGY BY THE ART ASSOCIATION OF AUSTRALIA AND NEW ZEALAND *How has Asia been imagined, represented and transferred both literally and visually across linguistic, geopolitical and cultural boundaries? This book explores the shifting roles of those who produce, critique and translate creative forms and practices, for which distinctions of geography, ethnicity, tradition and modernity have become fluid. Drawing on accounts of modern and contemporary art, film, literature, fashion and performance, it challenges established assumptions of the cultural products of Asia.Special attention is given to the role of cultural translators or 'long-distance cultural specialists' whose works bridge or traverse different worlds, with the inclusion of essays by three important artists who share personal accounts of their experiences creating and showing artworks that negotiate diverse cultural contexts.With contributions from key scholars of Asian art and culture, including art historian John Clark and anthropologist Clare Harris, alongside fresh voices in the field, Asia Through Art and Anthropology will be essential reading for students and scholars of anthropology, art history, Asian studies, visual and cultural studies. The publication of the color plates of works by Phaptawan Suwannakudt and Savanhdary Vongpoothorn is funded by the Australian Government.